Cover Feature: Modular Construction of Porous Hydrogen‐Bonded Molecular Materials from Melams (Chem. Eur. J. 31/2020). Issue 31 (30th April 2020) - Khadivjam, Tinasadat; Che‐Quang, Huy; Maris, Thierry; Ajoyan, Zvart; Howarth, Ashlee J.; Wuest, James D.
Abstract : Melams, which are derivatives of bis(4, 6‐diamino‐1, 3, 5‐triazin‐2‐yl)amine, can form multiple intermolecular N−H⋅⋅⋅N hydrogen bonds and serve as modules for constructing hydrogen‐bonded organic frameworks (HOFs). This work shows that suitably designed melams can crystallize to form open networks in which each molecule engages in over 20 N−H⋅⋅⋅N hydrogen bonds, more than 70% of the volume is available for accommodating guests, and guests can be removed to create rigorously porous crystalline solids. More information can be found in the Full Paper by J. D. Wuest et al. on page 7026 .